Pseudofenestration of the Cervical Internal Carotid Artery: A Pathologic Process that Simulates an Anatomic Variant - Gailloud, Philippe; Carpenter, Jeffrey; Heck, Donald V.; Murphy, Kieran J. (American Journal of Neuroradiology, 2004)
Summary: Fenestration of the cervical segment of the internal carotid artery (ICA) is considered an extremely rare anatomic variant, with, to the best of our knowledge, only four cases reported in the literature. We report six angiographic observations of apparent fenestration of the cervical ICA, which we believe are secondary to arterial dissection. We discuss the angiographic appearance of these pseudofenestrations and their potential clinical implications.